IMPROVING MARKET UNDERSTANDING IN PROVIDING INNOVATED PRODUCTS FOR - Suganda, Uce Karna (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze and discuss the effect of network capability and marketing intelligence on product innovation through marketing misx. The population in this study were SMEs in West Bandung district. Researchers used 211 samples. The data collection technique used a questionnaire. Data were analyzed using path analysis. In the test results, the variable path analysis measure is the variable network capability and marketing intelligence that has an effect on product innovation through the marketing mix. This research emphasizes to SMEs the importance of network influence and market-related understanding in providing innovative products. The limitation in this study is that the sample obtained in Bandung Regency is 211. Further research can be carried out in different cities with more samples from this study.